Measurement of the Top-Quark Mass in the All-Hadronic Channel using the full CDF data set - Collaboration, CDF; Aaltonen, T; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (American Physical Society, 2014)
The top-quark mass M_top is measured using top quark-antiquark pairs produced in proton-antiproton collisions at a center-of-mass energy of 1.96 TeV and decaying into a fully hadronic final state. The full data set collected with the CDFII detector at the Fermilab Tevatron Collider, corresponding to an integrated luminosity of 9.3 fb-1, is used. Events are selected that have six to eight jets, at least one of which is identified as having originated from a b quark. In addition, a multivariate algorithm, containing multiple kinematic variables as inputs, is used to discriminate signal events from background events due to QCD multijet production. Templates for the reconstructed top-quark mass are combined in a likelihood fit to measure M_top with a simultaneous calibration of the jet-energy scale. A value of M_top = 175.07+- 1.19(stat)+1.55-1.58(syst) GeV/c^2 is obtained for the top-quark mass.